Alternativas para el control del salivazo (Mahanarva andigena), en el cultivo de caña de azúcar (Saccharum officinarum). - Santana Suárez, Marcelo Joel (2022)
This bibliographic compilation details the different alternatives for the control of spittlebug (Mahanarva andigena), in the cultivation of sugar cane (Saccharum officinarum). Among the alternatives are those of biological, cultural, etiological and chemical control, which influence the control of this pest that is the cause of economic losses to sugarcane growers. The conclusions determine that a relatively stable environment of sugarcane plantations can sometimes favor the establishment of natural control by native parasitoids and predators or biological control by introduced beneficial species; There are various agronomic practices that help prevent or minimize pest damage preventively, where an integrated pest management program will be successful if preventive control practices are included; Sugarcane cultivation is exposed to multiple and varied pest species, and more than one species may attack simultaneously. In turn, the development and application of rational control tactics tend to be specific, although there are several exceptions. In these circumstances, producers have broad-spectrum synthetic pesticides within their reach, however, the use of Metarhizium anisopliae is in a development phase, but there are good prospects for its use in management programs for this pest, especially during the rainy season. According to preliminary studies, a dose of 1 x 1013 conidia/ha is recommended, which is equivalent to 2 to 3 kg of rice-fungus/ha.